The Formation of Cluster Systems of Education in the Russian Federation - Mindlin, Yurii B.; Melnichuk, Marina V.; Lisichkina, Yulia S.; Golovanova, Natalia B.; Litvinova, Svetlana F. (International Review of Management and Marketing, 2016)
If we assume that the cluster is an organizational form of uniting the efforts of stakeholders towards achieving competitive advantages, the combination of entities should be based on complementarity of intellectual, infrastructural and material resources. The modern world functions and develops in several interrelated, interdependent and interrelated planes (directions), which are called media: ethno-religious, cultural, moral, socio-political, industrial-technological, economic-labor, geopolitical, etc. Each environment can be considered as a holistic system, if it includes some required components. Localization and physical infrastructure create the conditions for the existence of the environment. The content and process define the scope of human existence, which is specific to your environment. Information and methods of communication (the full details of the two previous components) to provide individual environment for each person. This component of the environment is a kind of field, making it accessible and connecting with other mediums. In the framework of the education cluster may be a system of national priorities of the Russian Federation, to determine the sequence of emergency stocks, will be finding the most cost effective ways of solving environmental problems, which is especially important in the conditions of rigid financial policy. Coordination of the joint efforts of all actors and components of the educational cluster – guarantee of successful solution of tasks of Federal importance in Russia. Keywords: resource management, system management, cluster, educational cluster JEL Classifications: I21, I25, I28